Estandarizacion de un Elisa para la deteccion de anticuerpos a Bronquitis infecciosa aviar - Cuello, S.=700 1 Noda, J.; Perera, C.L.; Alfonso, P.; Nuñez, A.; Acosta, I.
(En, Es)
Ilus., 16 ref.
Keywords: AVES DE CORRAL; BRONQUITIS; ANTIGENOS; DIAGNOSTICO; TECNICAS ANALITICAS; ANTICUERPOS; CUBA; ELISA; REVISTA DE SALUD ANIMAL